KEPEMIMPINAN TRANSFORMASIONAL SEKRETARIS DAERAH KABUPATEN PARIGI MOUTONG - Ikram, Mohamad (Katalogis, 2015)
The main focus of this research is transformational leadership of regional secretary. This research aims to find out the transformational leadership and supporting and barrier factors of the leadership of regional secretary of Parigi Moutong Regency. Theory used was transformational leadership theory from Bernard M. Bass who formulated it into four aspects as main condition of the successfulness of transformational leadership process, namely individual concern,intellectual stimulation, inspirational motivation and idealized influence. This research employed a qualitative research. The informant was officials of regional secretariat area determined purposifely in sampling. The data collections were observation, interview and documentation. The data analysis was data reduction,data display and drawing conclusion (verification). The research result reveals that transformational leadership of regional secretary had not been fully done as the theory determined because there were there aspects were not effective. Only aspect of inspirational motivation gives good response towards the transformational leadership. It was shown by the implementation of activities which in every part always presented repeatedly through meetings, morning and afternoom gathering and ceremonies.